A comparison of the nationally important infection prevention and control documents in NHS England and NHS Scotland. Issue 2 (March 2021) - Curran, Evonne T; Burnett, Emma; Robinson, Jude; Loveday, Heather
Background: The devolution of health to Scotland in 1999, led for the first time in the NHS, to different priorities and success indicators for infection prevention and control (IPC). This project sought to understand, compare and evaluate the national IPC priorities and available indicators of success. Aim: To identify the national IPC priorities alongside national indicators of success. Methods: Critical analysis of nationally produced documents and publicly available infection-related data up to March 2018. Findings: For both NHS Scotland and England the local and national IPC priorities are evidenced by: (1) people being cared for in an IPC-safe environment; (2) staff following IPC-safe procedures; and (3) organisations continuously striving not just to attain standards, but to improve on them. If national agencies that produce data were also charged with using a Continuous Quality Improvement (CQI) model, then there would be further opportunities to detect and improve on successes.